Perlindungan Hukum terhadap Anak di Daratan Timor Provinsi Nusa Tenggara Timur - Josshy Christine Dudu; Deby F.Ng. Fallo; Rosalind Angel Fanggi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research aims to find out and analyze the legal protection of children in East Nusa Tenggara Province. This research is an empirical legal research using primary and secondary data collected using interview techniques , questionnaires, and literature studies and analyzed in a qualitative descriptive manner. The results of the study show that children in mainland Timor face various forms of interrelated violence, including physical violence that causes injury, psychological violence that damages mental health, sexual violence that causes deep trauma, and social violence in the form of neglect, hindering the fulfillment of children's basic rights, so the government needs to make preventive and repressive efforts in providing legal protection efforts.